Taraxacum pudicum, a new apomictic microspecies of T. section Erythrosperma (Asteraceae) from Central Europe - Vašut, Radim J.; Majeský, Ľuboš (Phytotaxa, 2015)
A new species of apomictic lesser dandelions, Taraxacum pudicum Vašut & Majeský is described. This species is a triploid diplosporous apomict, it belongs to the T. scanicum group and grows in the SE part of Central Europe, with the highest frequency found in southern Bohemia and Moravia. Species characteristics, notes on ecology and chorology are given. The relationship to other taxa and the controversy surrounding the description of apomictic species are discussed in this paper.